SAT0229 The use of antimalarial drugs during pregnancy can prevent the development of preeclampsia in women with systemic lupus erythematosus. (15th June 2017) - Saavedra, MA; Miranda-Hernández, D; Lara-Mejía, A; Sánchez, A; Cruz-Reyes, CV; Angeles, U; Jara, LJ
Abstract : Background: The antimalarial drugs decrease the risk of lupus activity during gestation, but the beneficial effect on other maternal-fetal complications is controversial. Objectives: To analyze the beneficial effect of antimalarial drugs on maternal-fetal complications in pregnant women with systemic lupus erythematosus (SLE). Methods: A prospective cohort of pregnant women with SLE (ACR 1997) from January 2009 to June 2015 was studied. The patients were assessed every 4 to 6 weeks and postpartum both, by a rheumatologist and a gynecologist. Clinical, biochemical, and immunological characteristics, along with maternal and fetal complications were registered. For analysis, the patients were allocated to one of two groups: pregnancies exposed to antimalarial drugs in comparison to those not exposed. A logistic regression analysis including variables such as smoking, obesity, infections, first pregnancy, age, SLE flare, drugs (prednisone, antimalarials, aspirin, and azathioprine), anti-DNA antibodies, anticardiolipin antibodies, and antiphospholipid syndrome was performed. Results: We studied 197 lupus pregnancies, 154 expose to antimalarial drugs and 47 unexposed. We found no differences between groups in age, years of evolution of SLE, first pregnancy, childhood-onset SLE, lupus nephritis, and use of prednisone, aspirin and azathioprine. The rate of most maternal and fetal complications was also similar in both groups (Table). A lower incidence of preeclampsia was observed in patients exposed to antimalarial drugs compared to those not exposed (9% vs 23%, p=0.01). Additionally, 2 maternal deaths in patients not exposed to antimalarial drugs. The logistic regression analysis showed that the use of antimalarial drugs during pregnancy is a protective factor for the development of preeclampsia (RR 0.1, 95% CI 0.05–0.58, p=0.004); on the other hand, active SLE before pregnancy (RR 4.8, 95% CI 1.3–17.8, p=0.01) and lupus nephritis (RR 2.9, 95% CI 0.9–8.8, p=0.05) were associated factors with the development of preeclampsia. Conclusions: Our study suggests that the use of antimalarial drugs during pregnancy can prevent the development of preeclampsia in women with SLE. Disclosure of Interest: None declared